Tanggungjawab Perusahaan Ekspedisi terhadap Kerusakan dan Kehilangan Barang Muatan dalam Pengangkutan Darat - Ketut Arie Jaya; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2020)
Responsibilities of Freight Forwarding Companies in commercial transportation are not easy where risks and events such as damage and loss that occur on cargo goods are very vulnerable to occur so that the Expedition Company suffers losses. This study aims to analyze the factors that cause damage and loss of cargo in land transportation and determine the responsibility of shipping companies for damage and loss of cargo in commercial transportation agreements on land. The method used in this study is an empirical research method with a sociological approach to law. There are two types of data used in this study, namely primary data and secondary data. The technique used in data collection is interviews conducted with informants in the Expedition Company, PT. Indah Cargo Logistic, Denpasar. The results showed that there were two factors that caused the transportation of damaged or missing items, namely system error, cashier error, administration, shrinkage, fraud or fraud from company staff. Label or address attachment error. While external factors include natural factors such as bad weather or rain, traffic accidents, thieve factors, damaged road factors that cause goods to become damaged in the car. From the results of this study, it recommends that the principle of responsibility due to errors and the principle of responsibility due to presumption is very appropriate to be applied in the activities of transporting goods in Indonesia because in addition to protecting the interests of the sender and recipient of goods also gives a sense of security to the transporter in carrying out his duties.